Automated Python Code Explanation Using AI: Enhancing Code Comprehension for Developers - Aastha Kulkarni; J. S. Awati; M. S. Kumbhar (Advance Research in Communication Engineering and its Innovations, 2024)
This paper introduces the "Python Code Explainer", an AI-driven tool designed to generate human-readable explanations for Python code automatically. Using Natural Language Processing (NLP), the system translates code into understandable descriptions, helping developers quickly grasp functionality without requiring extensive comments. The tool is evaluated for accuracy and effectiveness in improving code comprehension, offering a solution for streamlined documentation and enhanced code readability. As software systems grow complex, developers need tools to simplify code understanding. Automated Python code explanation using AI enhances comprehension by translating code semantics into clear, natural language descriptions. This paper presents an AI-driven system that explains Python constructs, including loops and functions, adapting to user expertise. Influencing machine learning and natural language processing, it bridges the gap between code syntax and intent, aiding learning, debugging, and collaboration. The approach reduces cognitive load, boosting productivity and fostering efficient software development.